Acetylene carbonylation over Ni-containing catalysts: role of surface structure and active site distribution. Issue 99 (11th October 2016) - Xie, Hao; Lin, Tiejun; Shi, Li; Meng, Xuan
Abstract : Traditional homogeneous catalyst with heterogeneous Ni catalysts (Ni-ZSM-5, Ni-IM-5 and Ni-MCM-41) for acetylene carbonylation. Using proper parameters to confirm the influence of surface structure and active site distribution on performance. Abstract : Heterogenization of homogeneous catalyst for acetylene carbonylation was carried out by preparing a series of Ni-modified catalysts (Ni-ZSM-5, Ni-IM-5 and Ni-MCM-41). Several important properties of the heterogeneous catalysts were determined by inductively coupled plasma atomic emission spectroscopy (ICP-AES), XPS, XRD, N2 adsorption, pyridine-FTIR, SEM and TGA. Moreover, we used various activity criteria to dissipate perturbing factors, when we focused on the influence of surface structure and active site distribution. The result that Ni-IM-5 had the greatest TOFNi = 5107 g acrylic acid per g Ni per h showed that the surface structure of samples did not influence the catalyst performance significantly. In addition, the highest ratio of nickel sites/acid sites in Ni-MCM-41 represented the best active site distribution. Thus, Ni-MCM-41 has the highest TOFcat = 70.6 g acrylic acid per g cat. per h. Furthermore, stability testing of the catalysts showed the Ni-MCM-41 could be used four times, while others only twice.